The development of the Egyptian Weightlifting Federation in light of the Total Quality Management - عادل عبدالمنعم محمد مكي; عبادة خالد عبدالرؤوف إبراهيم; فرج مصطفى عنتر زيدان (Journal of Sport Science Technology and Physical Activities, 2017)
This study was conducted in 2016. The study aimed to develop the proposed vision for the development of the Egyptian Weightlifting Federation in light of the overall concept of quality as he used the researchers descriptive approach and questionnaire and interviews obstacle to the collection associated with the study data, reaching the study sample (54) Single workers in Federation Weightlifting and branches of him and he was chosen the way random sample intentional, and the most important conclusions of this study, the lack of application for the overall quality and the lack of adequate recognition to employees the concepts and principles of total quality, and the most important recommendations of the study need to apply the proposed model for the development of the Egyptian Weightlifting Federation in light of the Total quality management and work on implementing the necessary personnel to implement comprehensive quality training courses.